3(4k+14)=10k-2(k-14)

Simple and best practice solution for 3(4k+14)=10k-2(k-14) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(4k+14)=10k-2(k-14) equation:


Simplifying
3(4k + 14) = 10k + -2(k + -14)

Reorder the terms:
3(14 + 4k) = 10k + -2(k + -14)
(14 * 3 + 4k * 3) = 10k + -2(k + -14)
(42 + 12k) = 10k + -2(k + -14)

Reorder the terms:
42 + 12k = 10k + -2(-14 + k)
42 + 12k = 10k + (-14 * -2 + k * -2)
42 + 12k = 10k + (28 + -2k)

Reorder the terms:
42 + 12k = 28 + 10k + -2k

Combine like terms: 10k + -2k = 8k
42 + 12k = 28 + 8k

Solving
42 + 12k = 28 + 8k

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '-8k' to each side of the equation.
42 + 12k + -8k = 28 + 8k + -8k

Combine like terms: 12k + -8k = 4k
42 + 4k = 28 + 8k + -8k

Combine like terms: 8k + -8k = 0
42 + 4k = 28 + 0
42 + 4k = 28

Add '-42' to each side of the equation.
42 + -42 + 4k = 28 + -42

Combine like terms: 42 + -42 = 0
0 + 4k = 28 + -42
4k = 28 + -42

Combine like terms: 28 + -42 = -14
4k = -14

Divide each side by '4'.
k = -3.5

Simplifying
k = -3.5

See similar equations:

| 5x^2*6x=0 | | 1/5(3x^2-10)=12x | | 1/5(3x^2-10)=12 | | 1/5/9+4/1/-6 | | 15/9+41/-6 | | -14+a=10 | | 27x^2-15x+2= | | 16x^2+24+9= | | (x+3)/(x^2-2x)-10/(x^2-4) | | 30x^3+129x^2+84x=0 | | 30x^3+129x^2+84=0 | | 2/7x=2/9 | | 4-(3-1)2= | | x^2-2x^2-3x=0 | | w+9+3w=8+10w | | f(x)=x^3-2x^2-3x | | (3x)/(x^2+4x+3)+2/(x^2-1)=(4x)/(x^2+2-3) | | v^2+14v+40=0 | | -x^2-10x+144=0 | | s^2+8s=9 | | 4m^2-21m+27=0 | | 7u^2-19=324 | | 10x+570=5620 | | 10(5)+570=y | | 1/9(4t-4)=t+4/18 | | 9x-(3x+5)=3x-23 | | 18/3+2*6+7 | | 1/8(8t-5)=t+5/16 | | 10(2)+570=y | | 10(0)+570=y | | 4b-7=-14 | | 2x^2+3=4x+7 |

Equations solver categories